Periodontitis association with IL-8 gene polymorphisms - Kriauciunas, Albertas; Zekonis, Gediminas; Liutkeviciene, Rasa (Biomedical papers, 2022)
IL-8 and its polymorphisms are involved in multiple acute and chronic inflammatory processes including pathological changes to surrounding structures of the teeth called periodontal diseases or periodontitis. The aim of this manuscript was to systematically review studies from 2006 to 2021 on IL-8 polymorphisms and their association with periodontitis. Literature analysis was done following the PRISMA protocol guidance using articles not older than 15 years (2006-2021). The search was carried out using PubMed (MEDLINE), ScienceDirect and Wiley Online Library databases. For the focus question, the PICO (population (P), intervention (I), control (C), and outcome (O)) study design protocol was used, and the following question was formulated: are IL-8 gene polymorphisms associated with periodontitis? A total of 2422 articles were found at the beginning of the search. After applying the inclusion and exclusion criteria, screening, and full-text article exclusion with reasons, 31 studies were included in the analysis. In conclusion, IL-8 and its gene polymorphisms are associated with an increased risk of periodontal diseases.
Keywords: periodontitis; IL-8; gene polymorphisms; serum level; literature review; PRISMA protocol guidance